The Role of Translation Paratexts in the Representation of the Other: Annotation and Iconographic Aspects in the Spanish Editions of The Pillow Book by Sei Shōnagon - Serra-Vilella, Alba; Rodríguez Navarro, María Teresa (TRANS: Revista de Traductología, 2025)
The Pillow Book by Sei Shōnagon is a classical Japanese text that has been published in Spain in four different translations, three into Spanish and one into Catalan. The paratexts display considerable differences in the presentation of the Other. This paper, therefore, aims to shed light on the images shaped by the translators and publishers. In addition, the factors that may be related to a domesticating or exoticizing image in the corpus of notes are examined. The results show that time and the translator’s degree of expertise and cultural knowledge, as well as their visibility are all factors related to the type of image that is offered.